L-arginine-etched nickel-silver electrocatalyst for low-potential hydrogen evolution - Zhang, Yan; Wu, Jindong; Zhu, Xinrui; Ren, Zhi; Chen, Jiean (Applied catalysis. B, Environmental, 2024)
The oxidation of formaldehyde at low potentials to achieve anodic hydrogen production is a crucial focus of current research. Copper-based alloys are prominent electrocatalysts in these reactions but face long-term stability challenges and are susceptible to CO intermediate poisoning. A novel approach that utilizes L-arginine in the surface modification of nickel foam substrates has been developed, enabling the highly dispersed deposition of silver catalysts on the substrates as sub-nanometer particles. This modified electrocatalyst allows formaldehyde oxidation and water electrolysis at a minimal potential of 0.32 VRHE and bipolar hydrogen production with near 100% Faradaic efficiency. This surface modification of substrate material provides a new approach to the design of electrodes. [Display omitted] •Surface Modification of Nickel Foam for Enhanced Performance.•Low-Loading Ag Nanoparticle Catalyst.•Bipolar Hydrogen Production by Oxidation of Formaldehyde and Electrolysis of Water.•Mechanism of Ag0 Catalysis.